Pengaruh Keputusan Investasi, Pendanaan, dan Dividen Terhadap Nilai Perusahaan Periode 2014-2018 - Fajriatul Mubarokah; Novi Permata Indah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Infrastructure, utilities and transportation are one of the sectors that have been supported by President Joko Widodo since 2014, but the factors that influence in increasing the value of the company experience fluctuating movements until the end of 2018. Research with objects of the infrastructure, utilities and transportation sector companies still rarely found. The purpose of this study was to determine the effect of investment decisions (PER), funding (DER), and dividends (DPR) on the company value (PBV) of the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange for the 2014-2018 period. The analytical method used in this research is quantitative descriptive and verification using multiple linear regression models. Based on the results of hypothesis testing conducted by researchers using the Statistical Product and Service Solutions (SPSS) 24 application, investment and funding decisions have a significant effect on firm value, while dividends do not significantly influence firm value. Simultaneously note that investment decisions, funding, and dividends significantly influence the value of the company. The coefficient of determination is 76.6%.